Development of Internet-Based SCADA Prototype for Substation Power Protection System - MOHAMAD REZAL, MUHAMMAD KHALAF FAHMI; Lam Hong Yin (Progress in Engineering Application and Technology, 2024)
This project aims to improve the efficiency and safety of electricity distribution networks by developing an automated monitoring system. The main purpose is to gather and send essential electrical information including voltage, current, power, and temperature in real time. This information is crucial for identifying and addressing any issues in the power supply network. The system incorporates a relay mechanism, which acts as a safeguard, triggering when electrical parameters exceed pre-set thresholds. The project employs ESP32, a microcontroller, Adafruit INA219 current sensor, AHT10, temperature sensor, for the coordination of various substation system sensors. Those sensors continuously measure and acquired updated real time data on a live substation system for the monitoring on Human Machine Interface on Blynk.